U-Shaped Development: An Old but Unsolved Problem - Pauls, Franz; Macha, Thorsten; Petermann, Franz (Frontiers in Psychology, 2013)
Even today the investigation of U-shaped functions in human development is of considerable importance for different domains of Developmental Psychology. More and more scientific researchers focus their efforts on the challenge to describe and explain the phenomenon by identifying those skills and abilities being affected. The impact of U-shaped functions on diagnostic decision-making and on therapeutic treatment programs highlights the importance of understanding the nature of nonmonotonic development. The present article therefore addresses the relevant questions of how U-shaped functions are defined in theory, in which developmental domains such nonmonotonic growth curves are suggested to occur, and which implications there are for future methodology and diagnostic practice. Finally, it is recommended to clearly identify those interactions between proximal and distal subcomponents which are expected to contribute to a U-shaped development.